Nuevos registros de tigrillo (leopardus wiedii) en San Luis Potosí, México - Martínez-Calderas, Jesús M.; Rosas-Rosas, Octavio C.; Palacio Núñez, Jorge; Martínez-Montoya, Juan F.; Villordo Galván, Jorge A. (Instituto de Ecología, A.C., 2012)
We documented 36 new records of tigrillo in the region Huasteca of San Luis Potosí, México. This new evidence of tigrillo presence augments its range within the state 38 km west. Records were found mainly in areas with dense vegetation cover including tropical forest and tropical deciduous forest. Results of this investigation suggest tigrillo mainly inhabits areas with dense vegetation cover in this region of Mexico.